The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/sim.8075
|View full text |Cite
|
Sign up to set email alerts
|

Should a propensity score model be super? The utility of ensemble procedures for causal adjustment

Abstract: In investigations of the effect of treatment on outcome, the propensity score is a tool to eliminate imbalance in the distribution of confounding variables between treatment groups. Recent work has suggested that Super Learner, an ensemble method, outperforms logistic regression in nonlinear settings; however, experience with real‐data analyses tends to show overfitting of the propensity score model using this approach. We investigated a wide range of simulated settings of varying complexities including simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…This issue may be related to the estimation of more extreme PSs values obtained with GBM, which could undermine the positivity assumption. These findings agree with the study of Alam and colleagues [ 82 ] who observed better covariate balance and lower bias when PS was estimated with LR or Super Learner than GBM.…”
Section: Discussionsupporting
confidence: 93%
“…This issue may be related to the estimation of more extreme PSs values obtained with GBM, which could undermine the positivity assumption. These findings agree with the study of Alam and colleagues [ 82 ] who observed better covariate balance and lower bias when PS was estimated with LR or Super Learner than GBM.…”
Section: Discussionsupporting
confidence: 93%
“…Our method can also be adapted and extended to settings where different strategies for confounding adjustment, such as inverse probability weighting or matching, may be preferred. 21,22 Overall, this article introduces a flexible framework for incorporating observational data in prospective trial design, providing an empirical framework to support decision-making in pragmatic trials.…”
Section: Discussionmentioning
confidence: 99%
“…In small samples and when the overlap in the distribution of propensity scores is poor, a propensity score-adjusted regression model is preferable to matching, stratification, or weighting. [20][21][22]…”
Section: Confounding Adjustmentmentioning
confidence: 99%
“…For this reason, automatic variable selection approaches (eg, stepwise) or prediction-based measures of fit (eg, C-statistic), which seek best prediction of treatment allocation when specifying the PS model, may not provide the best balance for the confounders and favor variables that are strongly predictive of the treatment, even if they are only weakly or not at all predictive of the outcome. 22…”
Section: Initial Data Summary and The Propensity Scorementioning
confidence: 99%